1993
DOI: 10.1126/science.262.5141.1852
|View full text |Cite
|
Sign up to set email alerts
|

The Transition State of the F + H 2 Reaction

Abstract: The transition state region of the F + H(2) reaction has been studied by photoelectron spectroscopy of FH(2)(-). New para and normal FH(2)(-)photoelectron spectra have been measured in refined experiments and are compared here with exact three-dimensional quantum reactive scattering simulations that use an accurate new ab initio potential energy surface for F + H(2). The detailed agreement that is obtained between this fully ab initio theory and experiment is unprecedented for the F + H(2) reaction and suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
156
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(160 citation statements)
references
References 50 publications
3
156
0
Order By: Relevance
“…The FH 2 Ϫ photoelectron spectrum study provided a useful meaning to directly probe the potential energy surface near the transition state region, which might shed light on the reaction resonance in the system. Indeed, the experiment not only observed signal due to the resonance in the reaction but also discovered direct evidence that the F ϩ H 2 reaction has a bend transition state (18). However, because of limited experimental resolution, the experiment could not resolve the signal associated with the reaction resonance and hence did not supply any new clue to the dynamical origin of the HF(vЈ ϭ 3) forward scattering product in the F ϩ H 2 3 HF ϩ H reaction.…”
mentioning
confidence: 99%
“…The FH 2 Ϫ photoelectron spectrum study provided a useful meaning to directly probe the potential energy surface near the transition state region, which might shed light on the reaction resonance in the system. Indeed, the experiment not only observed signal due to the resonance in the reaction but also discovered direct evidence that the F ϩ H 2 reaction has a bend transition state (18). However, because of limited experimental resolution, the experiment could not resolve the signal associated with the reaction resonance and hence did not supply any new clue to the dynamical origin of the HF(vЈ ϭ 3) forward scattering product in the F ϩ H 2 3 HF ϩ H reaction.…”
mentioning
confidence: 99%
“…Examples where the power of this spectroscopy has been demonstrated include F + H 2 , 3,4 Cl + H 2 /D 2 , 7 X + HX (X, X = F, Cl, Br, I). [8][9][10][11] The extension to the X + CH 4 reactions, where X is a halogen, is currently underway in the laboratory of Neumark 12,13 for F and Cl and also by us.…”
mentioning
confidence: 99%
“…This showed that in the case of the F-CH 4 system the vertical transition from the anion ground state to the neutral potentials accesses a region between the vdW valley and transition state of the early-barrier F + CH 4 Photodetachment spectroscopy of a stable anion to produce a neutral reactive system has been proven to be a powerful probe of key properties of the reactive potential energy surface, such as the pre-reactive van der Waals (vdW) well and/or the reaction transition state (TS). [1][2][3][4][5][6][7] The sensitivity of this technique to probe these aspects of the reactive potential depends on the position of the anion vibrational wave function with respect to the vdW well and/or TS.…”
mentioning
confidence: 99%
“…A mixture of this "indirect" mechanism was generally believed to lead to the shifting of the "direct" backward-scattering mechanism to forward-scattering for HF(v′ = 3). More recent experimental work, which directly probes the F + H 2 transition state region, and increasingly high-level ab initio calculations of the potential energy surface have forced a revision of this interpretation (25). The new results indicate that it is the precise shape of the PES in the transition state region that is responsible for the forward scattering.…”
Section: Crossed-molecular-beam Methodsmentioning
confidence: 99%
“…A typical chamber is illustrated schematically in Figure 6. By the 1980s, crossed-beam studies had matured sufficiently to allow Y. T. Lee and coworkers to produce a beautifully detailed experimental study of the reaction of F + H 2 , a reaction that has become a benchmark in the field of reaction dynamics (25). The mass spectrometer is rather insensitive to the internal state of the product, but the kinematics of the F + H 2 system enabled the vibrational resolution of the angular scattering of the HF products, as illustrated in Figure 5.…”
Section: Crossed-molecular-beam Methodsmentioning
confidence: 99%